An Overview of in vivo Functions of Chondroitin Sulfate and Dermatan Sulfate Revealed by Their Deficient Mice - Mizumoto, Shuji; Yamada, Shuhei (Frontiers in Cell and Developmental Biology, 2021)
Chondroitin sulfate (CS), dermatan sulfate (DS) and heparan sulfate (HS) are covalently attached to specific core proteins to form proteoglycans in their biosynthetic pathways. They are constructed through the stepwise addition of respective monosaccharides by various glycosyltransferases and maturated by epimerases as well as sulfotransferases. Structural diversities of CS/DS and HS are essential for their various biological activities including cell signaling, cell proliferation, tissue morphogenesis, and interactions with a variety of growth factors as well as cytokines. Studies using mice deficient in enzymes responsible for the biosynthesis of the CS/DS and HS chains of proteoglycans have demonstrated their essential functions. Chondroitin synthase 1-deficient mice are viable, but exhibit chondrodysplasia, progression of the bifurcation of digits, delayed endochondral ossification, and reduced bone density. DS-epimerase 1-deficient mice show thicker collagen fibrils in the dermis and hypodermis, and spina bifida. These observations suggest that CS/DS are essential for skeletal development as well as the assembly of collagen fibrils in the skin, and that their respective knockout mice can be utilized as models for human genetic disorders with mutations in chondroitin synthase 1 and DS-epimerase 1. This review provides a comprehensive overview of mice deficient in CS/DS biosyntheses.